10-(4-Hydroxy-6-methyl-2-oxo-2H-pyran-3-yl)-3-methyl-1H, 10H-pyrano[4, 3-b] chromen-1-ones from a pseudo-multicomponent reaction and evaluation of their antioxidant activity. Issue 8 (22nd February 2018) - Saher, Liza; Makhloufi-Chebli, Malika; Dermeche, Leila; Dermeche, Samia; Boutemeur-Khedis, Baya; Rabia, Cherifa; Hamdi, Maamar; Silva, Artur M.S.
Abstract: A series of novel 10-(4-hydroxy-6-methyl-2-oxo-2 H -pyran-3-yl)-3-methyl-1 H, 10 H -pyrano[4, 3- b ]chromen-1-ones were synthesized by a pseudo-three-component reaction of 4-hydroxy-6-methyl-2-oxo-2 H -pyran-2-one (TAL) with 2-hydroxyarylaldehydes using different acids as catalysts and solvents. The approach relies on a regioselective cascade reaction involving two molar equiv of the TAL iteratively acting as active methylene in a Knoevenagel condensation and in a Michael addition. The antioxidant activity of the synthesized compounds were determined using the DPPH scavenging assay, being the results dependent on the nature and number of chromone substituents. The compound bearing an ortho -dihydroxy (catechol) moiety showed excellent activity at lower concentrations, while derivatives bearing alkoxy groups as substituents present pro-oxidant activity. Graphical abstract: